Moral landscapes and morally meaningful encounters: how interaction ritual connects conversation analysis and cultural sociology - Horgan, Mervyn (Frontiers in Sociology, 2024)
This article presents a theoretical argument for examining the previously unexamined interface between the strong program in cultural sociology ethnomethodology/conversation analysis (EMCA). While these two approaches have radically different theoretical and empirical commitments, they nonetheless share a common root in Durkheim’s sociology, specifically with regard to the centrality of solidarity, ritual, and morality to collective life. Similarly rooted in Durkheim, Goffman’s theory of interaction ritual provides an analytic pivot between EMCA and the strong program. The broader theoretical argument is illustrated using data from interviews with adults about their most recent encounter with a rude strangers in public space, which are here treated a breaches of the interaction ritual of civil inattention. Members readily draw on the specifics of a particular stranger interaction gone awry to reflect on the nature of life in public and to expound on their understandings of the ethics of face-to-face interaction and everyday morality more generally. Where EMCA focuses on the discoverability of the organizational features of everyday interaction, the position developed here is concerned with the organization of members’ interpretations of everyday interaction. While centered on specific kinds of interactional breaches, by finding common ground between EMCA and cultural sociology, the argument advances a potentially more broadly applicable approach that treats everyday encounters as morally meaningful and everyday lifeworlds as moral landscapes. Developing a comprehensive understanding of copresent interaction as a basic building block of society requires attention to both the organizational dynamics of copresent encounters and to the interpretive resources that ordinary members use to account for and justify their own and others’ conduct.